The Influence of Job Insecurity and Career Development on Employee Loyalty at Informa PTC Palembang - Welly, Muhammad; Roswaty, Roswaty; Purnamasari, Endah Dewi (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the influence of job insecurity and career development on employee loyalty at Informa PTC Palembang. The research employs a quantitative approach with a saturated sampling technique, where all 95 employees in the population were included as respondents. Data were collected through questionnaires and analyzed using statistical tests, including partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²). The results indicate that job insecurity and career development significantly influence employee loyalty both partially and simultaneously. The coefficient of determination shows that 27.9% of the variation in employee loyalty is explained by these variables, while the remaining 72.1% is influenced by other factors outside the research model. The findings suggest that the company should focus on managing job insecurity and strengthening career development programs to enhance employee loyalty Keywords : Job Insecurity, Career Development, Employee Loyalty